The creative economy in the State of São Paulo - Adduci, Cássia Chrispiniano; Araújo, Alda Regina Ferreira de; Novais, Luis Fernando (Brazilian Journal of Operations & Production Management, 2018)
The text provides a definition of the creative economy chain of São Paulo, seeking to measure its contribution to the economy of the State of São Paulo. For an initial characterization, this article proposes a measurement based upon two perspectives, taking the year 2014 as a reference. The first approach analyzes the chain of the creative economy of São Paulo from the point of view of added value and formal employment and a second one is elaborated with a focus on the flow of international trade.